On the Coupling Imbalance of the UWB BLC in the 5G Low Noise Amplifier Design - Abouelnaga, Tamer G.; Abdallah, Esmat A. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
In this article, the design and the development of ultra-wideband UWB branch-line couplers BLCs with a novel method to control the coupling imbalance are proposed. The proposed UWB BLC is suitable for the 5G low-noise amplifier (LNA) design. UWB 4-branch BLC is designed using design curves developed using even and odd mode analyses to cover the 5G (3.3-5 GHz) frequency bands. The vertical branches of the UWB BLC are replaced by modified ones, and their effect on the coupling imbalance is investigated. The proposed BLC occupies an area of 33.9 × 15.7 mm2 Both conventional and modified BLC are fabricated, and their measured S-parameters are compared with analytical and simulated models. Based on the balanced amplifier topology, a 5G UWB low-noise amplifier is designed. The proposed BLCs and the MGF3022AM InGaP-HBT (Heterojunction Bipolar Transistor) are used to produce acceptable UWB performance. The balanced amplifier return loss, noise figure, and gain are investigated as BLCs coupling imbalance varies. The ultra-wideband LNA exhibits an acceptable small-signal gain, noise figure, input return loss, and output return loss across the 5G different frequency bands.